2006
DOI: 10.1111/j.1360-0443.2006.01457.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of exercise in reducing desire to smoke and cigarette withdrawal symptoms is not caused by distraction

Abstract: The effect of exercise in reducing desire to smoke and cigarette withdrawal symptoms is not caused by distraction J Z Daniel, M Cropley and C Fife-Schaw AbstractAims and design Moderate intensity exercise has been shown to reduce common smoking withdrawal symptoms and desire to smoke in acutely abstinent smokers. The aim of the present study was to determine if this was caused by distraction. A secondary aim was to determine whether exercise-related changes in affect were related to reduction in symptoms.Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
51
0
9

Year Published

2008
2008
2019
2019

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 60 publications
(64 citation statements)
references
References 16 publications
3
51
0
9
Order By: Relevance
“…The programs have contributed to public health education, propagated innovative methods to reduce smoking in public health leaders and encouraging them towards further educational and interventional activity. Most studies base their analysis on measures for preventing the initiation of smoking, and only a small amount deal with the problem of smoking cessation [27]. There are also psychological symptoms associated with withdrawal, such as depression, nervous tension, fits of anger, or fatigue [28].…”
Section: Discussionmentioning
confidence: 99%
“…The programs have contributed to public health education, propagated innovative methods to reduce smoking in public health leaders and encouraging them towards further educational and interventional activity. Most studies base their analysis on measures for preventing the initiation of smoking, and only a small amount deal with the problem of smoking cessation [27]. There are also psychological symptoms associated with withdrawal, such as depression, nervous tension, fits of anger, or fatigue [28].…”
Section: Discussionmentioning
confidence: 99%
“…However, a literature search only identified one study assessing the effects of distraction during smoking abstinence. This study found no effects of a cognitive distraction task on cravings or withdrawal symptoms (Daniel et al 2006). There is evidence that thought suppression may result in increased thinking about smoking (Salkovskis and Reynolds 1994), and habitual use of thought suppression has been associated with greater difficulty quitting smoking (Toll et al 2001).…”
Section: Introductionmentioning
confidence: 96%
“…Two additional studies concluded the effect of PA was irrespective of the intensity level (moderate vs. vigorous). Further, the mechanism by which PA reduces desire to smoke and nicotine withdrawal symptoms is distinct from simple cognitive distraction (Daniel et al, 2006).…”
Section: Introductionmentioning
confidence: 99%